Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài

Những câu hỏi liên quan
Jim Mina Too
Xem chi tiết
huongkarry
Xem chi tiết
Nguyễn Anh Kim Hân
26 tháng 6 2018 lúc 9:28

\(\frac{1}{1+\sqrt{2}+\sqrt{3}}\)

\(=\frac{1+\sqrt{2}-\sqrt{3}}{\left(1+\sqrt{2}+\sqrt{3}\right)\left(1+\sqrt{2}-\sqrt{3}\right)}\)

\(=\frac{1+\sqrt{2}-\sqrt{3}}{2\sqrt{2}}\)

\(=\frac{2+\sqrt{2}-\sqrt{6}}{4}\)

Arata Trinity Seven
Xem chi tiết
Nguyễn Hương Ly
Xem chi tiết
Nguyễn Hương Ly
Xem chi tiết
Linh Nguyen
Xem chi tiết
Nguyễn Thanh Hằng
3 tháng 8 2020 lúc 16:43

a/ \(\frac{1}{2+\sqrt{3}}-\frac{1}{2-\sqrt{3}}+5\sqrt{3}\)

\(=\frac{2-\sqrt{3}}{\left(2+\sqrt{3}\right)\left(2-\sqrt{3}\right)}-\frac{2+\sqrt{3}}{\left(2-\sqrt{3}\right)\left(2+\sqrt{3}\right)}+5\sqrt{3}\)

\(=\frac{2-\sqrt{3}}{4-3}-\frac{2+\sqrt{3}}{4-3}+5\sqrt{3}\)

\(=2-\sqrt{3}-2-\sqrt{3}+5\sqrt{3}\)

\(=3\sqrt{3}\)

Vậy..

Nguyễn Thanh Hằng
3 tháng 8 2020 lúc 16:45

b/ \(\frac{1}{\sqrt{5}+2}-\sqrt{9+4\sqrt{5}}\)

\(=\frac{1}{\sqrt{5}+2}-\sqrt{\left(\sqrt{5}+2\right)^2}\)

\(=\frac{1}{\sqrt{5}+2}-\left|\sqrt{5}+2\right|\)

\(=\frac{\sqrt{5}-2}{\left(\sqrt{5}-2\right)\left(\sqrt{5}+2\right)}-\sqrt{5}-2\)

\(=\sqrt{5}-2-\sqrt{5}-2\)

\(=-4\)

Vậy..

Nguyễn Trọng Kiên
Xem chi tiết
phan thị minh anh
Xem chi tiết
Lương Ngọc Anh
22 tháng 7 2016 lúc 12:00

Ta có: \(\frac{1}{\sqrt[3]{9}-\sqrt[3]{6}+\sqrt[3]{4}}=\)\(\frac{\sqrt[3]{3}+\sqrt[3]{2}}{\left(\sqrt[3]{2}+\sqrt[3]{3}\right)\left(\sqrt[3]{9}-\sqrt[3]{6}+\sqrt[3]{4}\right)}=\frac{\sqrt[3]{2}+\sqrt[3]{3}}{\left(\sqrt[3]{2}\right)^3+\left(\sqrt[3]{3}\right)^3}=\frac{\sqrt[3]{2}+\sqrt[3]{3}}{5}\)

Nguyễn Thùy Dương
Xem chi tiết
Akai Haruma
8 tháng 9 2019 lúc 11:15

Lời giải:

Ta có:

\(\frac{\sqrt{3}+\sqrt{5}}{(\sqrt{5}+1)(\sqrt{3}-1)}=\frac{(\sqrt{3}+\sqrt{5})(\sqrt{5}-1)(\sqrt{3}+1)}{(\sqrt{5}+1)(\sqrt{5}-1)(\sqrt{3}-1)(\sqrt{3}+1)}\)

\(=\frac{(\sqrt{3}+\sqrt{5})(\sqrt{5}-1)(\sqrt{3}+1)}{(5-1)(3-1)}=\frac{(\sqrt{3}+\sqrt{5})(\sqrt{5}-1)(\sqrt{3}+1)}{8}\)